2015
DOI: 10.1007/s13201-015-0269-z
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of nitrate in Tanzanian groundwater aquifers: A review

Abstract: More than 25 % of Tanzanian depends on groundwater as the main source of water for drinking, irrigation and industrial activities. The current trend of land use may lead to groundwater contamination and thus increasing risks associated with the usage of contaminated water. Nitrate is one of the contaminants resulting largely from anthropogenic activities that may find its way to the aquifers and thus threatening the quality of groundwater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 48 publications
3
32
0
1
Order By: Relevance
“…It would be interesting to ascertain how dilution of water by direct runoff mean in terms of SAs pollution by analysing key water quality parameters such as nitrate and faecal matters. A study in Arusha found that wells that were open to runoff were more polluted than those prevented from direct runoff and which were recharged by water that had filtered through the soil matrix (vadose zone) (Elisante and Muzuka 2015). Previous studies indicated that nitrate pollution was a major problem in groundwater (Nkotagu 1996b, c;Shemsanga et al 2017).…”
Section: Water Quality and Seasonal Variation In Salinity And Water Dmentioning
confidence: 99%
See 2 more Smart Citations
“…It would be interesting to ascertain how dilution of water by direct runoff mean in terms of SAs pollution by analysing key water quality parameters such as nitrate and faecal matters. A study in Arusha found that wells that were open to runoff were more polluted than those prevented from direct runoff and which were recharged by water that had filtered through the soil matrix (vadose zone) (Elisante and Muzuka 2015). Previous studies indicated that nitrate pollution was a major problem in groundwater (Nkotagu 1996b, c;Shemsanga et al 2017).…”
Section: Water Quality and Seasonal Variation In Salinity And Water Dmentioning
confidence: 99%
“…Locals, however, were unable to explain why there were such seasonal variations in salt content of the SDWs. The locals failed to link seasonal salt dilution due to recharge and subsequent concentrations with ET and over-abstraction during dry months, and the fact that at the peak of dry seasons, recharged water would have interacted with the soil/ rock matrices for a longer period (Elisante and Muzuka 2015). Generally, the seasonal salinity variation as observed by the locals would be affected by the direct recharge into the aquifers/wells during wet season (De Louw et al 2013;Shemsanga et al 2017).…”
Section: Water Quality and Seasonal Variation In Salinity And Water Dmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it was during this decade that Tanzania established its own water quality standards through the Tanzania Bureau of Standards (TBS, 2008). Some review articles have been written on the subject, including that by Byrceson et al (1990) which featured the East African Region by Mohamed (2003) which featured studies conducted between late 1970s to late 1990s and by Elisante and Muzuka (2015) which featured occurrence of nitrate in ground water aquifers, among others. However, no review has been done on studies conducted in the most recent decade (2006 to 2016).…”
Section: Review Of Water Quality Assessment Studies In Tanzania 2006 mentioning
confidence: 99%
“…Groundwater is commonly alternative water resources in areas where surface water is not accessible (Sungsitthisawad & Pitaksanurat, 2013). Ground water constitutes 97% of global fresh water (Bharti et al, 2011) whose quantity, quality, accessibility and recharge depend mostly on geology, geomorphology, land use and levels of precipitation (Elisante & Muzuka, 2015).…”
Section: Introductionmentioning
confidence: 99%